The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1472-6963-11-299
|View full text |Cite
|
Sign up to set email alerts
|

Different patient subgroup, different ranking? Which quality indicators do patients find important when choosing a hospital for hip- or knee arthroplasty?

Abstract: BackgroundPatients are increasingly expected to become active, critical consumers in healthcare. They can use comparative healthcare information presented on websites to make informed choices for healthcare providers. However, the use of this information has been limited so far. An obstacle can be that the information is not perceived as relevant by patients. Presenting only the most important quality indicators might improve the usefulness of this information. The aim of this study was to explore which qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…The importance of the medical specialist in health care decision making [13,30] and the need for information about specialists’ interpersonal and communication skills and expertise [14] is also revealed in other research. The availability of online doctor-rating websites is growing and these websites have gained popularity among patients internationally [31-34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of the medical specialist in health care decision making [13,30] and the need for information about specialists’ interpersonal and communication skills and expertise [14] is also revealed in other research. The availability of online doctor-rating websites is growing and these websites have gained popularity among patients internationally [31-34].…”
Section: Discussionmentioning
confidence: 99%
“…This stresses the importance of making information as easy to understand as possible. It has also been shown that people have different information needs depending on the disease or condition [13,38]. Whether preferences for how information should be presented also differ among diseases is yet unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors included the available CPI for hip and knee replacements in the Netherlands, which gave the name of the organisation and the clinical performance of the care providers. Formally, ‘distance’ and ‘reputation’ are not CPI, but they were included because they are important to patients [ 9 , 11 , 28 ]. In this sense, such information can be seen as part of the performance of the healthcare system.…”
Section: Methodsmentioning
confidence: 99%
“…American and British studies have shown that the actual use of CPI for hospital care is restricted to 4–14% of the consumers [ 5 , 6 ], while the idea of choice appeals to most consumers [ 7 ]. Several Dutch studies of CPI for total hip or knee replacements have been performed [ 8 - 11 ]. The patients in Moser and colleagues’ study considered CPI to be an additional source of information when they were preparing for a doctor’s appointment.…”
Section: Introductionmentioning
confidence: 99%